2021
DOI: 10.21203/rs.3.rs-236326/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects on self-efficacy, motivation and perceived barriers of an intervention targeting physical activity and sedentary behaviours in office workers: A cluster randomized control trial

Abstract: Background The importance of physical activity on health is clear, but changing behaviour is difficult. Successful interventions aiming to improve physical activity and reduce sedentary behaviour is therefore of importance. The aim of this study was to evaluate effects on motivation, self-efficacy and barriers to change behaviour from two different behavioral intervention focusing either on reducing sedentary behaviour or on increasing physical activity as compared to a waiting list control group Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…lengthy meetings at round-tables). Additionally, SB has become a habitual process because it is linked to diverse contexts and activities, such as work, and standing at work is perceived as uncomfortable [65][66][67]. Unsurprisingly, therefore, that others only found significant SB reductions on weekends [20,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lengthy meetings at round-tables). Additionally, SB has become a habitual process because it is linked to diverse contexts and activities, such as work, and standing at work is perceived as uncomfortable [65][66][67]. Unsurprisingly, therefore, that others only found significant SB reductions on weekends [20,26].…”
Section: Discussionmentioning
confidence: 99%
“…Additional to positive feedback, it might, hence, be important to still remind participants of their initial goals and general SB recommendations. Blom et al evaluated two personal counselling interventions and only found an increase in controlled and autonomous motivation after the physical activity intervention and not after the SB intervention [ 67 ]. It might be helpful to have another personal meeting in the middle of the intervention, to keep sending two FBMs per week, or to adapt the FBMs themselves, also with a greater focus on healthy alternative behaviours and reminding of SB recommendations.…”
Section: Discussionmentioning
confidence: 99%